Myocardial protection and early outcome of different coronary surgical techniques for diabetic patients with triple vessels - Lei, Yu (Ann Saudi Med, 2014)
BACKGROUND AND OBJECTIVES: For patients with diabetes and triple-vessel disease, coronary artery bypass grafting (CABG) surgery is a well-established procedure, but cardiopulmonary bypass support may also lead to severe complications to these patients. The aim of this study was to compare myocardial protection and early outcomes in patients with diabetes and triple-vessel disease following different coronary surgical techniques. DESIGN AND SETTINGS: Prospective randomized trial of patients treated at the First Affiliated Hospital of China Medical University over a 3-year period (2011–2013). METHODS: In a single-center randomized trial, 668 patients with diabetes and triple-vessel disease were randomly assigned to off-pump (OPCAB) (number [n]=222), on-pump beating heart (OnP-BH) (n=223), and conventional CABG (OnP) (n=223) between January 2011 and October 2013. Myocardial injury was assessed by measuring the serial release of cardiac troponin I (cTnI) preoperatively, 1 hour, 12 hours, 24 hours, and 72 hours postoperatively. The early outcomes were compared among these 3 groups. RESULTS: Preoperative characteristics of the patients in all 3 groups were similar. No significant difference was found regarding the number of anastomoses, the use of the internal thoracic artery, postoperative new-onset atrial fibrillation, hemodialysis, stroke, reoperation for bleeding, and infective complications in the 3 groups (P>.05). The complete revascularization, postoperative drainage loss, intra-aortic balloon pump support, blood requirements, postoperative myocardial infarction, pulmonary complications, gastrointestinal complications, inotropic requirements >24 hours, ventilation >24 hours, intensive care unit stay >24 hours, and in-hospital stay >7 days were significantly lower in the OPCAB group than in the other 2 groups (P<.05). In-hospital mortality was lower in the OPCAB group than in the other 2 groups, but no statistical difference was observed (P>.05). Preoperative cTnI in the 3 groups was similar (P>.05); however, the lowest cTnI value was noted in the OPCAB group, followed by the OnP group, and it was highest in the OnP-BH group 1 hour, 12 hours, 24 hours, and 72 hours postoperatively (P<.05). CONCLUSION: OPCAB is superior to the OnP-BH and OnP techniques in terms of postoperative complications and myocardial protection in patients with diabetes and triple-vessel disease. Myocardial injury in the OnP-BH group was significantly higher than that in the OnP group.